MODELING AND OPTIMIZING HUMAN RESOURCE MANAGEMENT EFFECTIVENESS BASED ON LOCAL WISDOM AND IT LITERACY - Mei Tri Listari; Soewarto Hardhienata; Dian Wulandari (Yayasan Education and Social Center, 2026)
The purpose of this research is to develop strategies to address problems related to Human Resource Management Effectiveness and to discover ways to implement strategies to improve Human Resource Management Effectiveness. The method used in this research is the POP-SDM Method, or Modeling and Optimization of Human Resource Management, which is a Qualitative Exploratory research approach combined with a Quantitative Descriptive or Quantitative Causal approach. The sample comprised 144 principals and teachers from private elementary schools in Bogor Regency who met the superior criteria (A Accreditation). The path coefficient for the Positive Indirect Effect of Personality on the Effectiveness of Human Resource Management through organizational climate is 0.325 (βy3). The path coefficient β = 0.353 falls in the moderate category. This data indicates a Positive Indirect Effect of Personality on the Effectiveness of Human Resource Management through Knowledge Management.